A Study Of MTHFR Gene Polymorphisms In Patients With Nonsyndromic Orofacial Clefts And Their Parents - Sumita Pal, (2009)
This thesis describes the association of two important MTHFR gene single nucleotide polymorphisms 677CT and 1298AC with orofacial clefts in the Malay population. Tesis ini menggambarkan perkaitan antara polimorfisme nukleotida tunggal (SNP) gen MTHFR 677CT dan 1298AC dengan rekahan orofacial dalam populasi Malayu